PSV-A-9 Reduction of Salmonella Reading Using a Dairy-Originated Probiotic Bacterium, Propionibacterium Freudenreichii in Combination with a Live Attenuated Salmonella Typhimurium Vaccine in Growing Turkeys. (21st September 2022) - Peichel, Claire; Manjankattil, Shijinarah; Dewi, Grace; Akhtar, Luna; Bina, Peter; Creek, Medora; Deniz, Kerem; Hobbs, John; Wichmann, Elaina; Feist, Emma; Schlosser, Mikayla; Johnson, Timothy J J; et al.
Abstract: The emergence of unusual foodborne outbreak-causing Salmonella Reading (SR) in turkey production warrants rapid control measures. The objective of the study was to prevent the cecal colonization and internal organ dissemination of SR in growing turkeys using a dairy-originated probiotic bacterium Propionibacterium freudenreichii (PF), a live attenuated Salmonella Typhimurium vaccine (VC; AviPro Megan Egg), or their combination (PF+VC). In each experiment, 30, day-old poults were allocated into five groups: negative control (NC), SR control (SC), VC, PF, and PF+VC. Poults in VC and PF+VC were vaccinated as per recommendations. The PF and PF+VC were supplemented with 5 log10 CFU/ml of PF through drinking water until sample collection. All turkeys except in the NC group were inoculated with 5 log10 CFU/mL of SR. Seven days after inoculation, ceca, crop, liver, and spleen were collected for SR enumeration and enrichment. Homogenized cecal samples were diluted and plated on Xylose Lysine Deoxycholate (XLD) agar, and plates were incubated at 37 o C for 24 hours. Liver, spleen, and crop samples were enriched in selenite cysteine broth and streaked on XLD plates for Salmonella identification after enrichment. Each group had 6 turkeys with 5 groups in each experiment (30 turkeys). The experiment was repeated 3 times (N=90). Data were analyzed using the PROC-MIXED procedure of SAS, and significance was detected at P< 0.05. All treatments were effective in reducing SR in growing turkeys. Compared to PC (4.0 log10 CFU/g), VC and PF+VC reduced SR by >3 log10 CFU/g, and PF alone resulted in a 1.7 log10 CFU/g reduction of SR (P< 0.05). The PF+VC was better than independent treatments in preventing SR dissemination to liver and spleen and crop survival. Results indicate that P. freudenreichii probiotic and S. Typhimurium vaccine effectively protect growing turkeys against the emerging outbreak-causing SR (USDA NIFA Food Safety & Defense #2020-67017-30787).